Public security in classical ancient greek political and legal thought (teachings of socrates, plato, aristotle) - Zahumenna, Yuliia (ScienceRise: Juridical Science, 2021)
The aim of the article is to carry out the theoretical and legal analysis of key features of general philosophical and special legal understanding and interpretation of human, social and state security problems in the history of political and legal scholars of ancient times, in particular on the basis of scientific research of ancient Greek authors, opinions of that period, against the background of widespread collective ideas about security as a state of social relations, the condition of human (social) life and/or a kind of social value, objects (spheres) of this security, as well as subjects and regulatory mechanisms to ensure the appropriate state of society and the state. It is shown, that the ancient Greek political and legal thought demonstrates a wide panorama of original views on the formation, development, functioning and guarantee of public and personal, internal and external, military and international, political and economic security in the context of political and legal concepts that reflect complex dialectics. and the interaction of the individual, society, law and the state. It has been found, that the ancient Greek political and legal thought raises questions about the essence of public security. The matter of public security is an essential function of the state, which is realized by it both in the external sphere (military and foreign political security) and within the country (internal or domestic political security). Developed at the theoretical and philosophical level, the idea of good governance (Democritus, Plato, Aristotle, Polybius) is the idea of guaranteeing its security: bad governance - the key to the decline and collapse of the state, the death of its citizens. The philosophical concepts of Socrates, Plato and Aristotle are the most fundamental for the further development of political and legal models of public security